Quantitative analysis of local microcirculation changes in early osteonecrosis of femoral head: DCE-MRI findings - Li, Pinxue; Xie, Congqin; Liu, Yubo; Wen, Zhentao; Nan, Shaokui; Yu, Fangyuan (Frontiers in Surgery, 2023)
Aim This study aims to quantitatively analyze the changes in local microcirculation in early osteonecrosis of the femoral head (ONFH) by dynamic contrast-enhanced (DCE) MRI and to explore the pathophysiological mechanism of early ONFH. Patients and Methods We selected 49 patients (98 hips) aged 21 to 59 years who were clinically diagnosed with early ONFH. A total of 77 femoral heads were diagnosed with different degrees of necrosis according to the Association Research Circulation Osseous (ARCO) staging system, and 21 femoral heads were judged to be completely healthy. All patients underwent DCE-MRI scanning. Pseudocolor images and time-signal intensity curves were generated by Tissue 4D processing software. The volume transfer constant (Ktrans), extracellular extravascular space, also known as vascular leakage (Ve), and transfer rate constant (Kep) of healthy and different areas of necrotic femoral heads were measured on perfusion parameter maps. Differences and characteristics of these parameters in healthy and different areas of necrotic femoral heads were analyzed. Results The signal accumulation of healthy femoral heads is lower than that of necrotic femoral heads in pseudocolor images. The time-signal intensity curve of healthy femoral heads is along the horizontal direction, while they all have upward trends for different areas of necrotic femoral heads. The mean value of Ktrans of healthy femoral heads was lower than the integration of necrotic, boundary and other areas (F=3.133, P=0.036). The Kep value of healthy femoral heads was higher than the integration of lesion areas (F=6.273, P=0.001). The mean Ve value of healthy femoral heads was smaller than that of the lesion areas (F=3.872, P=0.016). The comparisons of parameters between different areas and comparisons among healthy areas and lesion areas showed different results. Conclusion ONFH is a complex ischemic lesion caused by changes in local microcirculation. It mainly manifests as increased permeability of the vascular wall, blood stasis in the posterior circulation, high intraosseous pressure in the femoral head and decreased arterial blood flow. The application of DCE-MRI scanning in quantitatively analyzing the visual manifestations of microcirculation after early ONFH is an ideal method to study the microcirculation changes of necrotic femoral heads.